Globalisation, Geopolitics, and Gender in Professional Communication - Mullany, Louise; Schnurr, Stephanie (Routledge Research in Applied Professional Communication, 2023)
This edited collection investigates the linguistics of globalisation, geopolitics and gender in workplace cultures in a range of different contemporary international settings. The chapters examine how issues of globalisation, gender and geopolitics affect professionals in different workplace contexts, including domestic workers; IT professionals; teachers, university staff; engineers; entrepreneurs; CEOs of different corporates including locally based businesses as well as multinationals; farmers; co-operative leaders; NGO leaders; bloggers; healthcare assistants and caregivers. Taking different sociolinguistic approaches to exploring language and the geopolitics of gender at work in Dubai, Kuwait, Kenya, Uganda, Morocco, Nigeria, Malaysia, Turkey, Belgium, Switzerland, New Zealand, Uganda, the UK and the USA, each chapter focuses on a range of salient geopolitical issues which often have global applicability, but which may also be subject to more localised socio-cultural variation. The chapters critically discuss issues of gendered language, perceptions and representations of workplace cultures, discrimination, the role of gendered stereotyping and deeply ingrained socio-cultural myths about gender and the importance of examining the intersections of identity - all of which continue to persist as barriers to equality and inclusion in workplaces worldwide. Despite the variation and diversity in professions and geopolitical contexts captured across the chapters, remarkably similar issues of gender discrimination and persisting inequalities are identified and critically discussed, thus pointing to the global nature of these issues.